USING WAITING LINES THEORY TO SOLVE THE PROBLEM OF WAITING A CASE STUDY IN THE NATIONAL BANK OF IRAQ - Tech. Suhaila Juma Radi; Asst. Tech. Afrah Oudah Sabeeh; Prof. Dr. Safaa Mohammed Hadi (Scholar Express Journals, 2023)
The research aims to determine the advantages of queuing theory, and to describe how customers' waiting time can be counteracted and reduced. Queue models are used to resolve bottlenecks and queues in manufacturing and service delivery processes. The importance of the research came from the importance of the issue of these waiting lines and their connection to the nature of services provided to customers and the intensity of competition between those in charge of providing services. A set of queuing theory computational methods were used to find appropriate solutions to the waiting problem and improve the quality of the time spent by the customer receiving service at the National Bank of Iraq for the first time. The data used to solve the queuing models were collected through interviews and field visits. The research concluded that the use of queue models in the study sample bank leads to reducing the waiting time of customers in the queue to receive the service and strengthening the bank's position in providing the service as quickly as possible, as well as reducing costs through the optimal use of the capabilities of the employees who provide the service.
Keywords: Waiting Line; Arrival Rate; Capacity Uutilization